2016
DOI: 10.1016/j.celrep.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Programmed CD8α + DC Activation Enhances Combination Cancer Immunotherapy

Abstract: Summary Numerous synergistic cancer immunotherapy combinations have been identified, but the effects of relative dose timing are rarely considered. In established syngeneic mouse tumor models, we found that staggering IFNα administration after, rather than before or simultaneously with, serum-persistent IL-2 and tumor-specific antibody significantly increased long-term survival. Successful combination therapy required IFNα-induced activation of cross-presenting CD8α+ DCs following release of antigenic tumor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…Of particular note, premature administration of a type-I interferon was found to significantly inhibit the immune response to a protein vaccine antigen. This same general time dependence was observed for several other DC immunostimulatory agents [27]. …”
Section: Roles For Innate Antibody Effector Function In Priming a T Csupporting
confidence: 81%
See 2 more Smart Citations
“…Of particular note, premature administration of a type-I interferon was found to significantly inhibit the immune response to a protein vaccine antigen. This same general time dependence was observed for several other DC immunostimulatory agents [27]. …”
Section: Roles For Innate Antibody Effector Function In Priming a T Csupporting
confidence: 81%
“…If one were to administer a pharmacological pulse of dendritic cell stimulation, it would make the most sense to time it so as to coincide with maximal DC antigen loading. We indeed found this to be the case for several immunostimulatory molecules [27]. Coadministration of a type-I interferon with anti-TAA mAb was ineffective against large syngeneic tumors, but delay of the interferon to two days following the mAb administration led to a majority of cures after only two cycles of treatment (Figure 3C).…”
Section: Roles For Innate Antibody Effector Function In Priming a T Cmentioning
confidence: 59%
See 1 more Smart Citation
“…Though it is clear that dosing parameters have a significant impact on safety and therapeutic outcome [157], these challenges often cannot be solved by optimizing dosing and timing alone (e.g., lowering dose increases safety but lowers efficacy). Drug delivery technologies provide many potential solutions to these issues.…”
Section: Engineering Safer Local Therapiesmentioning
confidence: 99%
“…(31) In a three-component immunotherapy employing long half life IL-2, an anti-tumor mAb, and interferon-α (IFN-α), Tzeng et al demonstrated that the timing of administration of IFN-α, acting as a DC maturation stimulus, was critically important for treatment efficacy. (46) Optimal responses were only seen when IFN-α was delayed following the anti-tumor mAb/IL-2 treatment; this sequential treatment allowed for a bolus of immunogenic tumor debris to be taken up by DCs, which were then matured with IFN-α for optimal cross-priming of tumor reactive T cells. If DCs were matured prematurely by administering IFN-α prior to this tumor antigen uptake, therapy failed.…”
Section: Combination Treatments Recruiting Innate and Adaptive Immunitymentioning
confidence: 99%